A queuing theory model for e-health cloud applications. (8th May 2020) - Kumar, M. Sathish; Raja, M. Iyappa
A healthcare application plays a significant role in people's healthier life in recent times. Cloud computing is an ease technology that provides resources to users on demand. In high-performance computing, cloud has been outgrew technology for providing its services to e-health applications by pay-as-you-go model. Workload management for e-health applications in the cloud is one of the major areas to focus on to achieve availability in e-health cloud. To manage the workload, elasticity is the key characteristics where the workloads are scaled up and down on demand. This can be achieved by effectively allocating and de-allocating virtual machines (VM). Henceforth VM allocation and de-allocation are the major issues in e-health cloud. In this paper, a Markovian-based queueing model is presented to manage the elasticity of an e-health cloud. There are two conditions were analysed in which 'virtual machine is failed' and the 'virtual machine can be recovered' and 'cannot be recovered'. The proposed model helps to improve the virtual machine scaling without changing the type of machine.